IN-VITRO SCREENING OF SOME PLANT EXTRACTS FOR THEIR POTENTIAL ANTICANCER ACTIVITY - Ebrahim, Hassan Yahia; Osman, Shaimaa Abdelrheem; Haffez, Hesham Raffat; Hassan, Zeinab Abedltawab (African Journal of Traditional, Complementary and Alternative Medicines, 2020)
Background: Natural products have been shown to be reliable sources of anticancer medicines although there is still a consistent demand for new therapeutic natural products for cancer treatment with minimal side-effects. Materials and Methods: In this study, six plant extracts (Grevillea robusta; Euphorbia millii; Euphorbia royleana; Aloe grandidentata; Bauhinia corniculate; and Cassia fistula) were screened for the presence of phytochemical metabolites as saponins, tannins, cardiac glycosides, alkaloids, flavonoids, anthraquinones and sterols, using qualitative tests. Antiproliferative screening assay was performed on a panel of three cancer cell-lines (HepG-2, HCT-116 and MCF-7) using MTT assay, and cytotoxicity was determined using WI-38 human fibroblast cell- line. Results: Some plant extracts reduced cellular growth for the selected cancerous cell-lines. For example, E. royleana and A. grandidentata extracts reduced HepG-2 cellular growth with IC50 of 0.42 and 0.53μg/mL, respectively. Moreover, A. grandidentata and C. fistula reduced cellular growth of MCF-7 with IC50 of 0.37 and 0.67 μg/mL, respectively. Conclusion: E. royleana, A. grandidentata and C. fistula showed significant anti-proliferative activity against HepG-2 and MCF-7 cell-lines with non-cytotoxic nature. This suggests their potential role as anticancer agents against these types of cancer. The presence of flavonoids, sterols and anthraquinones may suggest their enhanced anti-proliferative activities. Therefore, this study has shed light on the possible use of these extracts as potential sources of natural products-based therapy for cancer.